A Click Chemistry Approach to Developing Molecularly Targeted DNA Scissors. Issue 70 (5th November 2020) - Lauria, Teresa; Slator, Creina; McKee, Vickie; Müller, Markus; Stazzoni, Samuele; Crisp, Antony L.; Carell, Thomas; Kellett, Andrew
Abstract: Nucleic acid click chemistry was used to prepare a family of chemically modified triplex forming oligonucleotides (TFOs) for application as a new gene‐targeted technology. Azide‐bearing phenanthrene ligands—designed to promote triplex stability and copper binding—were 'clicked' to alkyne‐modified parallel TFOs. Using this approach, a library of TFO hybrids was prepared and shown to effectively target purine‐rich genetic elements in vitro. Several of the hybrids provide significant stabilisation toward melting in parallel triplexes (>20 °C) and DNA damage can be triggered upon copper binding in the presence of added reductant. Therefore, the TFO and 'clicked' ligands work synergistically to provide sequence‐selectivity to the copper cutting unit which, in turn, confers high stabilisation to the DNA triplex. To extend the boundaries of this hybrid system further, a click chemistry‐based di ‐copper binding ligand was developed to accommodate designer ancillary ligands such as DPQ and DPPZ. When this ligand was inserted into a TFO, a dramatic improvement in targeted oxidative cleavage is afforded. Abstract : Nucleic acid click chemistry provides a new route for developing targeted chemical nucleases. By clicking intercalating phenanthrene ligands to parallel triplex forming oligonucleotides a new type of targeted DNA cutter was developed and tuning of this system enables enhanced stability and specific knockout.